Management of fibrosarcoma soft palate: A rare case report - Sinaga, Jakaria; Kurnia, Benny; Setiani, Lily (School of Medicine, Universitas Syiah Kuala, 2024)
Soft palate tumors can be categorized as benign or malignant, with malignant tumors being more common than benign ones. Up to 55% of intraoral tumors are found on the palate; thus, they are known as palatal tumors. Many causative or supporting factors may contribute to the development of palatal tumors, such as the long-term use of tobacco and alcohol. A final diagnosis of a palatal tumor is typically achieved through histological examination. This paper aims to present a case involving a patient diagnosed with palatal fibrosarcoma. The patient, a 39-year-old woman, was diagnosed with palatal fibrosarcoma and underwent treatment consisting of Mass Extirpation and Palatoplasty. Relevant evidence and literature were gathered through searches conducted on PubMed, Medline, and manual research. In this specific case, the surgical approach to excise the palatal tumor was determined based on factors such as its size and location. The diagnosis is based on a combination of the patient's medical history, physical examination, and further clinical assessment. Treatment for palatal tumors primarily involves surgery aimedat completely removing the tumor tissue.